2015
DOI: 10.3389/fphys.2015.00309
|View full text |Cite
|
Sign up to set email alerts
|

Lipid storage changes in human skeletal muscle during detraining

Abstract: Exercise training is known to increase intramuscular triglyceride content in both trained and untrained legs. The purpose of the study was to determine the changes of intramyocellular lipids (IMCL) and extramyocellular lipids (EMCL) of both trained and untrained legs during detraining. We measured both IMCL and EMCL levels in previously trained vs. untrained legs during 4-weeks of detraining after 6-weeks of strength training. Eight young men (aged 21.4 ± 1.4 years) trained their vastus lateralis muscle in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…28 Apart from the possible greater elevations of post-exercise EE and associated fat oxidation, high-intensity exercise-induced hydrocarbon source redistribution might have also potentially contributed to the greater reductions in AVFA observed in SITs and HIIT relative to that in MICT. 29,30 Indirect evidences have suggested that following exercise active muscles may transiently increase competition with adipose tissues, including abdominal fat depots, for circulating postprandial hydrocarbons from multiple sources (fat, carbohydrate, and protein) for tissue reconstruction, 31,32 and the extent of competition appears to be dependent upon exercise intensity. 29,30 The resultant greater partitioning of postprandial hydrocarbon-based nutrients into the active muscles may create apparent negative energy balance in the abdominal fat cells and promote the fat reduction.…”
Section: Discussionmentioning
confidence: 99%
“…28 Apart from the possible greater elevations of post-exercise EE and associated fat oxidation, high-intensity exercise-induced hydrocarbon source redistribution might have also potentially contributed to the greater reductions in AVFA observed in SITs and HIIT relative to that in MICT. 29,30 Indirect evidences have suggested that following exercise active muscles may transiently increase competition with adipose tissues, including abdominal fat depots, for circulating postprandial hydrocarbons from multiple sources (fat, carbohydrate, and protein) for tissue reconstruction, 31,32 and the extent of competition appears to be dependent upon exercise intensity. 29,30 The resultant greater partitioning of postprandial hydrocarbon-based nutrients into the active muscles may create apparent negative energy balance in the abdominal fat cells and promote the fat reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of these two pools is well established; however, their individual significance in skeletal muscle physiology is still not clear. Studies utilizing MRS demonstrated that different physiological states or interventions can affect the distribution -and perhaps the physiology -of imTG and emTG pools (28)(29)(30). Training resulted in a significant increase in imTG content with no change in emTG, while detraining resulted in a return of imTG content to the baseline with increased emTG content (29).…”
Section: Resultsmentioning
confidence: 99%
“…Studies utilizing MRS demonstrated that different physiological states or interventions can affect the distribution -and perhaps the physiology -of imTG and emTG pools (28)(29)(30). Training resulted in a significant increase in imTG content with no change in emTG, while detraining resulted in a return of imTG content to the baseline with increased emTG content (29). Rosiglitazone therapy decreased the imTG/emTG ratio by increasing the emTG pool size (30).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found a significantly lower ratio of IMAT 19 During detraining, the trained muscle also kept a higher myocellular lipid storage than untrained muscle. 20 In a previous study, we showed that children with JIA have a lower lipid oxidation rate during submaximal exercise than healthy peers. 21 Consequently, the lower IMAT content in children with JIA than in healthy children could be explained by a lower level of physical activity and a weakened oxidative metabolism.…”
Section: Structure and Quality Of Muscle In Children With Jiamentioning
confidence: 89%